(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Syntaxa diagnosed by species of Elytrigia Desv. (Elytrigia repens (L.) Nevski, E. elongatа (Host) Nevski, E. intermedia (Host) Nevski, E. nodosa (Nevski) Nevski, E. pseudocaesia (Pach.) Prokud., E. trichophora (Link) Nevski, E. strigosa (M.Bieb.) Nevski, E. scythica (Nevski) Nevski), E. bessarabica (Săvul. & Rayss) Prokud. are inventoried based on analysis of literature. Syntaxonomical content of the communities includes 48 associations from 25 alliances, 17 orders and 13 classes. A lot of the syntaxa are common and widespread (Elytrigio repentis-Aegopodietum podagrariae Tüxen 1967, Urtico dioicae-Tanacetum vulgaris Kostylev in V. Solomakha et al. 1992, Artemisietum vulgaris R. Tüxen 1942, Elytrigio repentis-Robinietum pseudoacaciae Smetana, Derpoluk, Krasova 1997, etc.) or occur sporadically (Acini arvensis-Elytrigietum intermediae (Kukovitsa at al. 1994) Kukovitsa in V. Solomakha 1995, Salvio nemorosae-Elytrigietum intermediae Tyschenko, 1996, Goniolimoni taurici-Poetum angustifoliae Tyschenko 1996, Limonio-Festucetum pseudodalmaticae V. Solomakha et Shelyag-Sosonko 1984 etc.) in Ukraine. An absolute majority of the studied coenoses are in a state of dynamic expansion, with the exception of some relatively rare communities (Elytrigio trichophorae-Poetum angustifoliae (Kostylev et al. 1984) V. Solomakha 1995, Adonidi-Stipetum tirsae Didukh 1983, Drabo cuspidatae-Potentilletum geoidis Ryff 2000, Laserpitio hispidi-Heracleetum stevenii Korzhenevsky et Ryff 2002, etc.) that are constantly threatened by ecotope elimination. Most of the communities (23 associations) are dominated by Elytrigia repens that has wide ecological amplitude.